(untitled) (International Journal of Engineering and Computer Science, 2017)
Cloud Computing can be described in terms of services which is being provided to users “pay as you go”. As a new technical field cloud is gaining attention due to continuous growth . With the help of internet, data and resources are shared between machines . As with cloud computing , if database services are being provided through it , then it can be called as Cloud Database . Nowadays DBaaS is upcoming new service in cloud computing scenario because more and more people now wish to save database work to cloud as they are affordable on low cost.